TRANSFORMASI PEMBANGUNAN DI KABUPATEN SANGGAU MELALUI RENCANA INDUK KELITBANGAN DAN KUALITAS RISET YANG UNGGUL - Christanto, Ludovicus Manditya Hari; Purnomo, Suharyo Joko; Farhan, Firda Islamaya (Academy of Education Journal, 2023)
The Research and Development Master Plan plays an important role in driving innovation and optimizing local government performance. Permendagri Number 17 of 2016 mandates the preparation of RIK as an R&D policy direction document that contains strategies and detailed program indications for five years. The aim is to provide input in the preparation of mid-term planning documents and accommodate the needs of Research and Development programs within the scope of Regional Government. It is necessary to formulate a comprehensive and synergistic research and development policy framework through Sanggau Regency RIK as a direction in supporting the acceleration of regional development that is right on target and competitive. The activity method used is the lecture approach, sharing, and outreach. RIK is expected to meet the expectations and needs of stakeholders in Sanggau Regency.